KINERJA PELAYANAN PEGAWAI NEGERI SIPIL DI SEKRETARIAT PEMERINTAH KABUPATEN ENREKANG - khaeriah Muh Diar; Muhlis Madani; Fatmawati Fatmawati (Department of Public Administration, Muhammadiyah University of Makassar, 2015)
The purpose of this research is to describe and explain the service performance of civil servants in the Government Secretariat in Enrekang Regency. The type of research is quantitative descriptive which describe the service performance of the employee. The respondent of the research are 63 employees selected by random sampling techniques. Techniques of the data collection use questionnaire and observation of the respondent. Analsys of the data use frequency tables. The results of this research are demonstrated by the highest percentage of the total fixed of the service performance employee with the percentage is 82.5 percent. There are inhibiting factors and supporting factors of the service performance employee. Inhibiting factors are quality of work, punctuality and discipline while supporting factors are motivation and work ability. Keywords: performance, services, employee Penelitian ini bertujuan untuk menggambarkan dan menjelaskan kinerja pelayanan pegawai negeri sipil di Sekretariat Pemerintah Kabupaten Enrekang. Jenis penelitian adalah deskriptif kuantitatif yang menjelaskan bagaimana kinerja pegawai terhadap pelayanan. Responden sebanyak 63 pegawai yang dipilih secara sampling acak. Teknik pengumpulan data menggunakan kuesioner dan observasi. Data tersebut dianalisis dengan menggunakan tabel frekuensi. Hasil penelitian ini dibuktikan dari persentase tertinggi yang tertuju pada uraian total frekuensi jadwal pelayanan pegawai dengan persentase tinggi 82,5 persen. Ada faktor pendukung dan penghambat pada kinerja pelayanan pegawai. Faktor penghambat yaitu kualitas kerja, ketepatan waktu dan kedisiplinan sedangkan faktor pendukung kinerja pelayanan pegawai yaitu motivasi kinerja dan kemampuan kerja. Kata kunci: kinerja, pelayanan, kepegawaian